Study of the underlying basis for valproate hepatotoxicity : drug metabolism and its interaction with homeostasis - Luís, Paula Maria Brazão Mendes, 1981- (2011)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2011